Study on crude oil displacement efficiency by fracturing fluid in tight sandstone reservoir - Jinfeng Li; Xingjun Gao; Lianru Yang; Jiashun Gong; Tezheng Duan; Fan Song; Jinsheng Zhao (PLoS ONE, 2025)
Tight sandstone reservoirs usually experience a long flowback period after hydraulic fracturing, which significantly affects oil production. After fracturing, the well-soaking is commonly employed to control fracturing fluid flowback and enhance oil recovery, so that the oil in the reservoir matrix is replaced by fracturing fluid, which can improve the crude oil recovery and reduce the flowback of the fracturing fluid. In this paper, the gel breaking fluid of slick water fracturing fluid, guanidine gum fracturing fluid and cross-linked guanidine gum fracturing fluid are used as displacement working fluids to study the effect of gel breaking fluid on oil displacement in tight sandstone reservoirs. The results show that it is not the smaller the pore radius that the higher the displacement efficiency, but the oil displacement efficiency is higher for the equilibrium of capillary force and percolation resistance in a certain radius of pore throat. For tight sandstone reservoir, the oil displacement efficiency of small pore, middle pore and large pore is higher, the oil displacement efficiency of micro-pore is lower, and the oil in pore throat with radius less than 0.01 μm is difficult to be replaced. The lower the interfacial tension is, the lower the viscosity is, and the higher the oil displacement efficiency is. For tight sandstone reservoir, the displacement efficiency of crude oil can reach 13.11% −33.31%, the displacement of crude oil in the early stage is mainly displaced out of the middle and small pores, and then replaced out of the large pores and micro-pores of crude oil.